Implementation of Teaching Factory (TEFA) in Vocational School to Improve Student Work Readiness - Kadek Diah Dwijayanthi; Tri Rijanto (Journal of Vocational Education Studies, 2022)
This research aims to find out the influence of teaching factory implementation on student work-readiness at SMKN 2 Singaraja. The type of research used is qualitative descriptive to find out phenomena related to the implementation of teaching factory. Interview, observation, and documentation methods are used to obtain data. Validity of data used in this study is the triangulation of sources. Data analysis is done in a way; (1) Data Reduction, (2) Presentation, and (3) Conclusion Drawing (Verification) after obtaining data on the ground. Results of this study showed that implementation of the teaching factory at SMKN 2 Singaraja has been quite good in terms of facilities, infrastructure, and industry involvement in the planning of TEFA activities. However, the TEFA implementation system implemented is less able to support student’s readiness, so there needs to be learning application models in implementation of TEFA that can improve student’s ability to think critically, and have a positive influence on work readiness supporting factors in students.